Professional Development of Rural Teachers Based on Digital Literacy - Hadi Soekamto; Irina Nikolaeva; Abbas Abd Ali Abbood; Denis Grachev; Mikhail Kosov; Alexey Yumashev; Evgeniy Kostyrin; Natalia Lazareva; Angelina Kvitkovskaja; Natalya Nikitina (Emerging Science Journal, 2022)
This research focuses on the professional development of teachers in rural areas based on digital literacy. It aims to measure the existing digital literacy and competence of rural teachers in Indonesia, Russia, and the Middle East and to assess the extent of digital literacy training provided to rural teachers for their professional development in these regions. In pursuit of this objective, a quantitative research method was incorporated into the study. The survey was conducted specifically for the research, and SPSS was used for statistical analysis. The report reflected the challenges that digitalization faces in rural areas and the differences in the provision of digital literacy training in Indonesia, Russia, and the Middle East. Various limitations are identified as hampering the integration of digital literacy in underdeveloped areas, such as the lack of proper digital infrastructure. However, the situation was found to be somewhat better in the case of Russia, with the teachers reporting the provision of adequate hardware and infrastructure, which were lacking in the cases of Indonesia and the Middle East. The same pattern was found in the case of the provision of digital literacy training opportunities in Indonesia and the Middle East, which lag behind Russia. All in all, it is imperative to develop introductory courses for using the internet and their general application for teachers in rural areas. Doi: 10.28991/ESJ-2022-06-06-019 Full Text: PDF